Does ESG Disclosure Enhance Firm Value? The Moderating Role of Profitability in Indonesia's ESG Leaders Index - Stefanny Wachyudi; Bagas Brian Pratama (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on firm value and analyze the role of profitability as a moderating variable in IDX ESG Leaders companies during the 2021–2025 period. This study uses a quantitative approach with secondary data obtained from annual reports, sustainability reports, and corporate financial statements. The sample was selected using purposive sampling, resulting in 15 companies with a total of 75 observations. Firm value is proxied by Tobin's Q, ESG disclosure is measured using an ESG disclosure index, while profitability is proxied by Return on Equity (ROE). The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that ESG disclosure has no significant effect on firm value, and profitability is unable to moderate this relationship. These findings indicate that, among IDX ESG Leaders companies, ESG disclosure tends to serve as a sustainability and legitimacy standard, but has not yet become a primary factor that directly increases firm value.